Paradigma Pendayagunaan Teknologi Informasi Menyongsong Masyarakat Global - K. B. Seminar (Jurnal Komunikasi Pembangunan, 2010)
In this global era, information technology (IT) has been aggressively developed and utilized for enhancing thevarious and dynamic needs of human beings in this world. This technology provides a new paradigm to individuals,groups, organizations, or business entities to interact, communicate, promote, share, invite, and cooperate to eachother electronically without space and time borders. However, the vital opportunity provided by IT must be smartlyand wisely responded by humans or organizations to achieve the best platform of implementation and utilization of ITto face the great challenge of globalization and competitiveness. The main mission of humans is to introduce worldwideprosperity, safety and sustainability for well beings. Therefore, the new paradigm for utilizing informationtechnology must focus on and comply with three pillars: (1) vision and mission of humans as the manager of earth,(2) the vision and mission of humans’ welfare & prosperity, and (3) vision and mission of enterprise/organization forrunning excellent business processes. This paper discusses various opportunities and strategies for utilizinginformation technologies for achieving the best performance and benefit to cope with global societies and challenges.